Penerapan Flashcard Digital dan Kuis Interaktif Menggunakan Media Pembelajaran Quizlet pada Pembelajaran Sifat-Sifat Benda di Kelas 3 SD/MI - Nurul Oktavia Ramadani; Ika Putra Viratama (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2026)
Natural Science (IPA) learning in elementary schools requires the use of learning media that is able to increase students' interest in learning, learning outcomes, and critical thinking skills. However, science learning is still often done conventionally, causing students to be less active and easily bored. Therefore, it is necessary to innovate learning media that is interactive and in accordance with technological developments. One of the digital learning media that can be used is the Quizlet application. This study aims to examine the application of digital flashcards and interactive quizzes using Quizlet learning media in learning the properties and changes of the form of objects in elementary schools. The research method used is a literature study by examining various relevant sources in the form of scientific journals, research articles, and supporting references related to the use of Quizlet in learning. The results of the study show that the use of Quizlet has a positive impact on the learning process, especially in increasing students' interest, activeness, and feelings of happiness during learning. Quizlet's flashcard and test features help students understand the material through engaging visual and audio-visual displays and varied practice questions. In addition, the use of Quizlet has also been proven to be able to improve students' critical thinking skills through question-answering activities, analyzing material, and providing opinions. Student learning outcomes showed an increase with an average score above the Minimum Completeness Criteria (KKM). Thus, Quizlet can be concluded as an effective, engaging, and relevant digital learning medium to support science learning in elementary schools.